Use of finite element analysis of a Lenke type 5 adolescent idiopathic scoliosis case to assess possible surgical outcomes. (May 2013) - Zhang, Hongqi; Hu, Xiheng; Wang, Yongfu; Yin, Xinhua; Tang, Mingxing; Guo, Chaofeng; Liu, Shaohua; Wang, Yuxiang; Deng, Ang; Liu, Jinyang; Wu, Jianhuang
<x xml:space="preserve">Abstract</x> Objective: To use the finite element model of a Lenke 5 adolescent idiopathic scoliosis (AIS) patient to simulate four corrections (including anterior and posterior correction); to investigate the corrective effect of different surgical protocols; and to analyze the biomechanical stress and strain of the scoliotic spines. Methods: Four surgical strategies were designed and simulated with the model of scoliosis. All the main steps of each strategy, including derotation and compression, were simulated. The stress variation of the spine and the corrective effect were compared among the protocols for different surgical approaches and fusion levels. Results: With the four different surgical protocols, the coronary lumbar deformity was corrected to 22°, 23°, 26° and 26°, respectively, and a physiological sagittal configuration was maintained; however, higher stress was observed with solutions A1 (screw model implanted in the convex side of T12-L3) and A2 (screw model implanted in the convex side of T11-L4), while solution B2 (the posterior approach: T10-L5, fusion to SV) lost too many lumbar movement segments. A similar apical rotational correction was recorded (41.68° and 37.79°) for solutions A2 and B1 (the posterior approach: T10-L4, fusion to LEV), which both instrumented the lower end vertebrae. Conclusions: The presented model could be used successfully to simulate correction procedures, including 90° derotation and compression, for the first time. The Lenke 5 AIS in this particular case was more rigid, and solution B1 was considered the ideal choice for treatment of this patient.